MODEL TATA KELOLA KELAS MINAT SENI HOLISTIK "PARAKLITA" SEBAGAI STRATEGI MITIGASI FENOMENA BLAST DAN PENGUATAN SELF-ESTEEM MURID DI SD CERDAS MUTHAHHARI BANDUNG - Hamdani, Rizki; Jaeni; Yahfenel Evi Fussalam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Arts education at the elementary level is often reduced to a ceremonial year-end performance, overlooking pupils’ psychological well-being. This article examines the "Paraklita" model, a holistic arts-management framework implemented through the cross-age, interest-based co-curricular program (Kelas Minat) at SD Cerdas Muthahhari (SCM), Bandung, functioning simultaneously as a professional festival-production system and a psychological mitigation strategy against the BLAST phenomenon (Bored, Lonely, Angry-Afraid, Stressed, Tired) commonly experienced by pupils under rigid academic pressure. Using a descriptive-analytical qualitative case study design, data were collected through document analysis (production proposals, budget plans, Kelas Minat curriculum records), participant observation, and informal interviews with key informants (the principal and program coordinators), then analyzed using Miles and Huberman’s interactive model. Findings show that professional-standard production management, planning, organizing, staffing, directing, and controlling, combined with teachers’ on-stage involvement as a psychological safety net, mitigates stage-anxiety-related trauma, generates the psychological state of Flow, and reinforces the six pillars of self-esteem, particularly self-assertiveness and self-acceptance. The model has remained resilient across three national curriculum shifts (KTSP, K-13, and Kurikulum Merdeka), suggesting that teacher-initiated, philosophically grounded arts management can be more stable than volatile top-down policy in sustaining pupils’ mental well-being and achievement.